WRONGFUL LIFE CLAIMS IN THE NETHERLANDS − THE HOGE RAAD DECIDES C03/206 HR JHM/RM - André Mukheibir (Obiter, 2022)
The Netherlands has always had a reputation for being more progressive than most societies. In addition to the booming prostitution trade and the ubiquitous coffee-shops where one may drop in for a whiff of cannabis without fearing prosecution, euthanasia was legalised in 2001 (after having been practised and tolerated (“gedoogd”) for many years prior to legalisation).The Hoge Raad has done it again with its decision in the Kelly case, in which a child, Kelly Molenaar, was awarded damages for the fact that she had been born with a severe handicap (Nr. C03/206HR JMH/RM, www.rechtspraak.nl).Ever since this case reached the lower courts, it has resulted in much publicity in both academic journals and the popular press. Awarding Kelly damages for being born with a handicap gave rise to several ethical problems, inter alia the fact that a child would in fact be claiming damages for the fact that it had not been aborted. Furthermore, one would invariably be faced with a comparison of the non-being of the child with its present state, something which is extremely problematic.In South Africa only one wrongful life claim has served before the courts, and it was turned down on the basis that it was against public policy (see par 6 below). The courts in England, Germany, Australia and the majority of states in the United States of America have also refused wrongful life claims.This note focuses on the Kelly case, and explores possible bases in South African law for a claim made on behalf of a handicapped child.